Appropriate doses of non-vitamin K antagonist oral anticoagulants in high-risk subgroups with atrial fibrillation: Systematic review and meta-analysis. Issue 4 (October 2018) - Kim, In-Soo; Kim, Hyun-Jung; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam
Highlights: Standard-dose non-vitamin K antagonist oral anticoagulants (NOACs) had better efficacy than warfarin in OAC-naïve patients. Standard-dose NOAC showed lower mortality than warfarin in OAC-naïve patients. Low-dose NOAC had better safety than warfarin in patients with previous stroke. Low-dose NOAC showed lower mortality than warfarin in patients with previous stroke. Abstract: Background: We evaluated the dose-dependent efficacy, safety, and all-cause mortality of non-vitamin K antagonist oral anticoagulants (NOACs) in "atrial fibrillation (AF) patients who were OAC-naïve, " or "AF patients with prior-stroke history" with those who were known to be high-risk subgroups under OAC. Methods: After a systematic database search (Medline, EMBASE, CENTRAL, SCOPUS, and Web of Science), five phase-III randomized trials comparing NOACs and warfarin in "OAC-naïve/OAC-experienced, " or "with/without prior-stroke history" subgroups were included. The outcomes were pooled using a random-effects model to determine the relative risk (RR) for stroke/systemic thromboembolism (SSTE), major bleeding, intracranial hemorrhage, and all-cause mortality. Results: 1. In OAC-naïve patients, standard-dose NOACs showed superior efficacy and safety with lower mortality [RR 0.90 (0.84–0.97), p = 0.008, I 2 = 0%] compared to warfarin. 2. For OAC-experienced patients, low-dose NOACs showed equivalent efficacy but reduced risk of major bleeding [RR 0.61 (0.40–0.91), p = 0.02, I 2 = 89%], and had lower all-cause mortality [RR 0.86 (0.75–0.99), p = 0.04, I 2 = 38%] compared to warfarin. 3. For patients with prior-stroke history, low-dose NOACs showed equivalent efficacy, but reduced risk of major bleeding [RR 0.58 (0.48–0.70), p < 0.001, I 2 = 0%] and all-cause mortality [RR 0.76 (0.66–0.88), p < 0.001, I 2 = 0%] compared to warfarin. 4. Among patients without prior-stroke history, standard-dose NOAC was superior to warfarin for both SSTE prevention [RR 0.78 (0.66–0.91), p = 0.002, I 2 = 43%] and all-cause mortality [RR 0.91 (0.85–0.97), p = 0.004, I 2 = 0%]. Conclusions: In conclusion, standard-dose NOAC showed lower all-cause mortality than warfarin in OAC-naïve patients with AF, and low-dose NOAC was better than warfarin among the patients with prior-stroke history in terms of all-cause mortality.